STRUCTURAL CHARACTERIZATION OF NATIVE SPECIES ACCORDING TO THE NEW BRAZILIAN STANDARD ABNT NBR 7190: 2022 - PART 4 - Moritani, Fabiana Yukiko; Icimoto, Felipe Hideyoshi; De Souza Nogueira, Rodrigo; Calil, Carlito; Dos Santos, Lorenzo Lube; Ballarin, Adriano Wagner [UNESP] (My University, 2023)
Timber is a heterogeneous material with high variability in its physical and mechanical characteristics. Therefore, whenever possible, it is essential to grade timber members using results from tests of structural size specimens that better express its structural quality to meet the design requirements. The Brazilian Standard ABNT NBR 7190: 2022 - Part 4, introduced test methods for mechanical characterization and strength grading of sawn timber in structural sizes. This study aimed to perform these mechanical tests for assign strength class for three native species of the Amazon rainforest obtained from trees under sustainable forest management (Caixeta (Simarouba amara Aubl.), Cedrinho (Erisma uncinatum Warm.), and Goiabão (Planchonella pachycarpa Pires.)). The Goiabão species had the highest characteristic value of bending strength and was graded as D60, Cedrinho D24, and Caixeta D18. Results also showed a high correlation (R2= 0.94) between modulus of elasticity in dynamic and static bending tests.
Keywords: Mechanical properties; Native species; Strength grading; Structural timber